Measuring the Success of SDGs Implementation Bonjeruk Village, Jonggat Sub-district, Central Lombok District, West Nusa Tenggara - Izana, Nyimas Nadya; Susanti, Anik (Sosioglobal : Jurnal Pemikiran dan Penelitian Sosiologi, 2025)
ABSTRACT Sustainable development has become a key strategy in addressing the challenges of economic inequality and environmental degradation at the village level. This study aims to assess the success of implementing the Village Sustainable Development Goals (SDGs) in Bonjeruk Village, Jonggat Sub-district, Central Lombok Regency, by focusing on community participation based on Cohen and Uphoff’s theory, which includes the dimensions of planning, implementation, utilization, and evaluation. A descriptive quantitative approach was applied by distributing closed-ended questionnaires using a Likert scale to 21 respondents selected through simple random sampling, supported by observations and interviews to strengthen the analysis. The results indicate that community participation is relatively high, particularly in the utilization stage of the tourism village program, with an average score of 3.37. This is reflected in the dominance of “agree” responses, where 52.4% of respondents acknowledged that village tourism activities contribute to economic welfare, 57.1% strongly agreed that information on tourism development programs is well communicated, and 52.4% confirmed the support of the village government through resource provision. The active involvement of the community in strategic planning, program implementation, economic benefit distribution, and program evaluation illustrates a collaborative success between the village government, the Tourism Awareness Group (Pokdarwis), and local communities. The findings suggest that structured and sustainable community participation through institutions, mechanisms, and clear regulations is the key to the successful implementation of the Village SDGs in Bonjeruk, positioning the village as a model for sustainable and collaborative tourism village development.Keywords: Village SDGs, community participation, Pokdarwis, tourism village  ABSTRAK Pembangunan berkelanjutan telah menjadi strategi utama dalam mengatasi tantangan ketimpangan ekonomi dan degradasi lingkungan di tingkat desa. Penelitian ini bertujuan untuk menilai keberhasilan implementasi Tujuan Pembangunan Berkelanjutan Desa (SDGs) di Desa Bonjeruk, Kecamatan Jonggat, Kabupaten Lombok Tengah, dengan berfokus pada partisipasi masyarakat berdasarkan teori Cohen dan Uphoff, yang meliputi dimensi perencanaan, pelaksanaan, pemanfaatan, dan evaluasi. Pendekatan kuantitatif deskriptif diterapkan dengan mendistribusikan kuesioner tertutup menggunakan skala Likert kepada 21 responden yang dipilih melalui simple random sampling, didukung oleh observasi dan wawancara untuk memperkuat analisis. Hasil penelitian menunjukkan bahwa partisipasi masyarakat relatif tinggi, khususnya pada tahap pemanfaatan program desa wisata, dengan skor rata-rata 3,37. Hal ini tercermin dari dominasi respons "setuju", di mana 52,4% responden mengakui bahwa kegiatan pariwisata desa berkontribusi pada kesejahteraan ekonomi, 57,1% sangat setuju bahwa informasi program pengembangan pariwisata dikomunikasikan dengan baik, dan 52,4% mengkonfirmasi dukungan pemerintah desa melalui penyediaan sumber daya. Keterlibatan aktif masyarakat dalam perencanaan strategis, pelaksanaan program, penyaluran manfaat ekonomi, dan evaluasi program menggambarkan keberhasilan kolaboratif antara pemerintah desa, Kelompok Sadar Pariwisata (Pokdarwis), dan masyarakat setempat. Temuan menunjukkan bahwa partisipasi masyarakat yang terstruktur dan berkelanjutan melalui kelembagaan, mekanisme, dan regulasi yang jelas adalah kunci keberhasilan implementasi SDGs Desa di Bonjeruk, memposisikan desa sebagai model pengembangan desa wisata yang berkelanjutan dan kolaboratif.Kata kunci: SDGs desa, partisipasi masyarakat, Pokdarwis, desa wisata